An analysis of intercultural bilingual education in Argentina. Issue 2 (3rd June 2014) - Carolina Hecht, Ana
Abstract : Purpose: – The purpose of this article is to assess the state of affairs of intercultural bilingual education (IBE) policies in Argentina. IBE encompasses educational proposals designed to address the specific needs of ethnolinguistic minorities. Design/methodology/approach: – The article is divided into three parts and methodologically analyzes different types of materials (national legislation, bibliography and personal research experiences). Findings: – In the first section, the educational policies on cultural and linguistic diversity are contextualized historically. Later, IBE is defined considering five main characteristics (the neoliberal compensatory education policy, educational decentralization/regionalization, the educational category of the system, linguistic goals and teacher profiles). Finally, the conclusions list the challenges, goals that have yet to be achieved and the future perspectives of this educational policy. Originality/value: – This article contributes to the field of studies on diversity in the schooling of ethnically different groups.